Accumulated Heat Unit and Phenology of Wheat Cultivars as Influenced by Late Sowing Heat Stress Condition - Sikder, S (Journal of Agriculture & Rural Development, 2010)
Accumulated heat unit and phenology of wheat (Triticum aestivum L.) cultivars were studied under normal and late sowing heat stress conditions by seeding them on November 30 and December 30, 2006. November 30 sowing was considered as normal sowing condition, whereas December 30 sowing was regarded as late sowing heat stress condition. Four heat tolerant wheat cultivars, Gourab, Sourav, Kanchan and Shatabdi and two heat sensitive cultivars, Sonora and Kalyansona were used as study materials. The results indicated that the number of days required to attain different phenological stages with late growing condition. For all the phenological stages plants of normal sowing condition needed higher heat units than the late sowing condition. At the earlier phenological stages phenothermal indices decreased with late sowing compared to normal sowing but increased at the later stages. At normal sowing condition all the cultivars showed higher heat use efficiencies compared to late sowing condition. The heat tolerant cultivars, Gourab, Sourav, Kanchan and Shatabdi exihited better performance in phenology, growing degree day, helio-thermal unit and finally used heat more efficiently than the heat sensitive cultivars, Sonora and Kalyansona. Key words: Wheat, phenology and heat use efficiency. DOI: 10.3329/jard.v7i1.4422 J Agric Rural Dev 7(1&2), 57-64, June 2009